Membership has its Privileges: On the Effects of Delegating Powers Internationally - Stefan Voigt (Universität Kassel, Fachbereich Wirtschaftswissenschaften, 2005)
This paper analyzes whether nation-state governments can increase their credibility by becoming members of international organizations. Credibility is an important asset because it determines the real interest rate and is expected to have an important impact on investment and growth. It is hypothesized that the degree of delegation to international organizations can improve the credibility of nation-state governments. This hypothesis is tested by introducing a new indicator. On the basis of 136 countries, various versions of an indicator of international delegation are highly significant for explaining variation in countries' credibility. The effect of international delegation on credibility is particularly strong among the group of lower income countries (N=60).
Keywords: P26; K33; F02; H11; F21; 330; Delegation of Competence; Credibility; Dilemma of the Strong State; International Organizations; Wirtschaftspolitik; Glaubwürdigkeit; Internationale Organisation; Mitgliedschaft; Länderrisiko; Schätzung; Welt